Formation mechanism of W phase and its effects on the mechanical properties of Mg−Dy−Zn alloys - J.S. Chen; C.J. Ji; Q.Y. Huang; Y.Z. Zeng; H.B. Xie; P. Chen; B.Z. Sun (Journal of Magnesium and Alloys)
The morphology and dimension of W phases play an important role in determining mechanical properties of Mg−RE−Zn (where RE denotes rare earth elements) alloys. In this study, the γ′ platelet and W particle occurred in the aged Mg−2Dy–0.5Zn (at.%) alloys were investigated by aberration-corrected scanning transmission electron microscopy. A novel formation mechanism of W phase was proposed, and its effects on the morphology and dimension of W particle, as well as mechanical properties of Mg−2Dy–0.5Zn alloys, were also discussed particularly. Different from other Mg−RE−Zn alloys, the nucleation and growth of W particle in Mg−Dy–Zn alloys mainly depend on the precipitated γ′ platelet. Primarily, a mass of Dy and Zn solute atoms concentrated near γ′ platelet or between two adjacent γ′ platelets can meet the composition requirement of W particle nucleation. Next, the smaller interfacial mismatch between W and γ′ facilitates the nucleation and growth of W particle. Thirdly, the growth of W particle can be achieved by consuming the surrounding γ′ platelets. The nucleation and growth mechanisms make W particles exhibit rectangular or leaf-like and remain at the nanoscale. The coexistence of γ′ platelets and nanoscale W particles, and some better interfacial relationships between phases, lead to a high strength-ductility synergy of alloy. The findings may provide some fundamental guidelines for the microstructure design and optimization of new-type Mg-based alloys.